Faktor Dominan Keterlambatan pada Proyek Konstruksi Gedung Bertingkat di Surabaya dengan Metode Relative Importance Index (RII) - Ninda Qurmaulia Dhani; Michella Beatrix (Prosiding Seminar Nasional Ilmu Teknik, 2025)
Delays in high-rise building construction projects in Surabaya are a crucial issue as they can significantly affect cost, quality, and project completion schedules. This reserach intends to identify the dominant factors contributing to project delays using the Relative Importance Index (RII) method, considering both frequency and impact aspects. Data were obtained from 80 valid respondents who hold strategic roles in construction project implementation, such as Project Managers, Site Managers, Site Engineers, Estimators, Field Supervisors, General Managers, and Company Directors. The analysis results indicate that in terms of frequency, the dominant factors are unfavorable weather conditions (RII = 0.750), labor shortages (RII = 0.743), and design changes during construction (RII = 0.735). Meanwhile, in terms of impact, the dominant factors are delays in material delivery (RII = 0.780), labor shortages (RII = 0.770), and substandard material quality (RII = 0.740). These findings emphasize that labor shortage consistently influences project delays in both frequency and impact, while weather and material factors show different patterns between occurrence and consequence. All dominant factors were classified into the High-Medium category, indicating that they should be prioritized in project risk management.